Comparison of Palm Oil and Rice Business Feasibilities: Study of Land Function Conversion Lubuk Pinang District, Mukomuko Regency - Alex Robinson Siagian; Ketut Sukiyono; Reswita Reswita (AGRITROPICA : Journal of Agricultural Sciences, 2022)
This study aims to (1) analyze the level of financial and non-financial feasibility of oil palm and rice farming, (2) analyze the sensitivity level of oil palm and rice farming, (3) determine the comparability of the feasibility of oil palm and rice farming and to know what is the most profitable in Lubuk Pinang District, Mukomuko Regency, Bengkulu Province. The data used in this study are primary data and secondary data. The sampling of oil palm farmers in this study used a stratified random sampling technique, while the rice farmers used accidental sampling techniques. The data analysis technique used in this study is the analysis of the Present Net Value (NPV) and Net B / C Ratio. The results showed that from a financial perspective, oil palm and rice farming in Lubuk Pinang District, Mukomuko Regency, Bengkulu Province, were declared feasible to continue; this can be seen from the NPV and B / C Ratio values. The NPV value in oil palm farming is IDR 44,682,270.66, while the NPV in rice farming is IDR 168,218,082.21. The Net B / C Ratio in oil palm farming was 2.31, while the Net B / C Ratio value in rice farming was 6.94. From a non-financial perspective, oil palm and rice farming are considered feasible due to the availability of production factors for both farms, such as seeds, labor, and other production inputs.